Avaliação do ensino e aprendizagem escolar: relações entre as políticas públicas de avaliação e a prática pedagógica - Fantinel, Cristiane Aparecida (2018)
The evaluation, continuous activity of analysis on the results achieved in contradiction with the determined objectives, generates movement in the process of teaching and learning in relation to methods and contents. Element of the educational action, it gained emphasis in educational public policies with the advent of neoliberalism. A broad and multifaceted theme, it is present in the daily life of school, permeated by constant questions about its function and its practice, in a meritocratic and exclusive social context. Facing this situation, we seek to investigate how the evaluation practices of primary school teachers, final years, are compared to the guidelines for the evaluation of school teaching and learning emanating from the public policies of evaluation for basic education. The investigation was delineated by a case study, with documental analysis and semi-structured interview. The analysis considered the socioeconomic and political reality which the data are related. In order to understand the relationship between public policies of evaluation and the evaluation practice of school teaching and learning, in the final years of elementary school in a state school in the city of Pato Branco / PR, we historicized evaluation and denoted the intrinsic relationship between the way of production of each historical period and the current educational model, which conditions the evaluative format according to the conception of hegemonic man, society and work, with greater emphasis in the late XX century, and the incidence of neoliberal perspectives, a condition that continues through the XXI century and influences education up to the present; we analyzed the public policies that guide the evaluation of school learning in the basic education of Paraná state with the study of the official documents and orientations coming from the management bodies of education, in which the neoliberal direction of the education was evidenced, promoting the merit perspective, promoting competition, classification and social exclusion, in which skills and abilities are valued rather than the scientific knowledge historically constructed, an evaluation policy in which attention is focused on raising indicators, controlling school through indexes, labor market training and maintenance of the perspective of education as a good to be acquired and consumed according to abilities and talents; and we analyzed the constitution of the evaluative practice of teaching and learning in the school context. We conclude that the public policies are incisive in the school organization and pedagogical practice, with influence in the construction of the school official documents and direction in the evaluation organization through the legislations, instructions, orientations, continued formations and programs. We emphasize the neotecnicist practice in the school routine, as well as the perception of neoconstrutivism as a salutary possibility to overcome this practice. We also emphasize, in the evaluation practice, the productivism, the quantification of knowledge and the process of blame assumed by the school community. Public policies of evaluation that influence pedagogical practice are evidenced, from a reductionist and controlling perspective of education, to the detriment of an education with social quality.